2016
DOI: 10.1161/jaha.116.003231
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Resistance Training as Stand‐Alone Antihypertensive Lifestyle Therapy: A Meta‐Analysis

Abstract: BackgroundAerobic exercise (AE) is recommended as first‐line antihypertensive lifestyle therapy based on strong evidence showing that it lowers blood pressure (BP) 5 to 7 mm Hg among adults with hypertension. Because of weaker evidence showing that dynamic resistance training (RT) reduces BP 2 to 3 mm Hg among adults with hypertension, it is recommended as adjuvant lifestyle therapy to AE training. Yet, existing evidence suggests that dynamic RT can lower BP as much or more than AE.Methods and ResultsWe meta‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
157
4
27

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(195 citation statements)
references
References 136 publications
(280 reference statements)
7
157
4
27
Order By: Relevance
“…The standardized mean difference effect size ( d ) was used to quantify the influence of exercise on cognitive function in adults at risk of or diagnosed with AD and has been described previously . Briefly, d values were calculated for exercise and control within‐group comparisons and exercise versus control between‐group comparisons, correcting for small sample size bias and, for the between‐group comparisons only, baseline differences . Multiple d values were calculated for 4 studies that involved more than 1 exercise intervention group (e.g., aerobic exercise training vs resistance training) and analyzed as independent studies .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standardized mean difference effect size ( d ) was used to quantify the influence of exercise on cognitive function in adults at risk of or diagnosed with AD and has been described previously . Briefly, d values were calculated for exercise and control within‐group comparisons and exercise versus control between‐group comparisons, correcting for small sample size bias and, for the between‐group comparisons only, baseline differences . Multiple d values were calculated for 4 studies that involved more than 1 exercise intervention group (e.g., aerobic exercise training vs resistance training) and analyzed as independent studies .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 2 studies that reported AD severity reported mild to severe AD, indicating a range of AD severity in their sample, and only 4 studies clearly indicated a sample with mild to moderate (k = 3) or severe (k = 1) AD. The moving constant technique was applied to estimate the magnitude of weighted mean effect sizes (d + ) and their CIs at different levels of interest for individual study–level moderators, including extreme values and other observations, within that range (see references for greater detail). Effects of continuous variables were held constant at their sample means by mean‐centering them and for categorical variables using contrast codes …”
Section: Methodsmentioning
confidence: 99%
“…Exercise has been long documented to improve blood pressure in obese individuals, even in the absence of weight loss 31, 32, 33. In 2004, studies from our institution indicated that blood pressure control, specifically recovery of poststress pressor increases, was correlated with high lean body mass in overweight subjects, arguing the skeletal muscle was an unappreciated determination of blood pressure control 34.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies demonstrate that the effects of physical exercise on blood pressure are dose‐dependent . Moreover, the beneficial effects depend on the type of exercise training . Importantly, resistance training is contraindicated in the presence of instable cardiovascular conditions, including uncontrolled severe hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] Moreover, the beneficial effects depend on the type of exercise training. [52][53][54][55][56][57][58] Importantly, resistance training is contraindicated in the presence of instable cardiovascular conditions, including uncontrolled severe hypertension. 59,60 Therefore, it is imperative to emphasize that a specific training plan including the specific type and dose of exercise training has to be delineated for each individual.…”
Section: Con Clus Ionsmentioning
confidence: 99%